Effect Of Banana Heart Consumption On Milk Production In Breastfeeding Mothers In The Working Area Of Rejosari Health Center Pringsewu Sub-District - Anggeilia Wananca Putri; Sukarni, Sukarni; Hikmah Ifayanti; Wulan dari (Jurnal EduHealth, 2025)
Rejosari Health Center, in 2023 the achievement of infants < 6 months getting breast milk exclusively is still below the national target of below 80% at 73.1%. One of the efforts to increase breast milk production is by consuming banana heart because it contains lactagogum substances that stimulate oxytocin and prolactin hormones to increase and facilitate breast milk production. This study aims to determine the effect of banana heart consumption on milk production in breastfeeding mothers. This type of quantitative research is a quasi-experimental design with a pretest-posttest approach with nonequivalent control group. The population of postpartum women on the fourth day was 23 people, the sample amounted to 20 people where 10 people in the intervention group and 10 people in the control group were taken by accidental sampling, when found by chance meeting the criteria immediately used as research samples. This study was conducted in the Rejosari Health Center working area by giving banana heart 2 times a day as much as 200 grams / day for 7 days to respondents. The average breast milk production of the intervention group before the intervention was 15 ml, to 86 ml after the intervention. The average pretest value of breast milk production of the control group was 11 ml, after posttet to 25 ml. The results of the Mann Whitney analysis showed that there was an effect of banana heart consumption on milk production expenditure in breastfeeding mothers with a p-value = 0.000, so it was concluded that there was an effect of banana heart consumption on milk production expenditure in breastfeeding mothers in the working area of the Rejosari Health Center, Pringsewu District in 2024 with a p-value = 0.000. It is expected that breastfeeding mothers utilize banana heart as a natural alternative that can support increased milk production, while still considering balanced nutritional intake and medical consultation.